Morphology of the third instar larva of Colobopterus quadratus (Coleoptera: Scarabaeidae: Aphodiinae) using scanning electron microscopy. Issue 8 (10th May 2019) - Li, Ce; Lu, Ying; Fang, Hong; Jiang, Lu
Abstract: Aphodiinae are a large cosmopolitan subfamily of Scarab beetles (Scarabaeoidea: Scarabaeidae), playing an important role during dung decomposition. Many aspects, especially immature stages, of these dung beetles have not yet been recorded due to their comparative small body sizes and lacking of striking rolling behavior. In this study, the third instar larva of Colobopterus quadratus is morphologically described using scanning electron microscopy. The larva is atypical for the combination of following morphological features: (a) the larval antennae are five‐segmented; (b) the clypeus bears 4 minute protuberances on dorsal surface; (c) the epitorma on epipharynx is ventrally protuberant; (d) the scissorial area of left mandible is broad and blade‐like; (e) the raster is furnished with six glabrous protuberances and two rows of pali arranged in V‐shape. Some significant ultra‐morphological features were discovered in larval Aphodiinae for the first time. The presence of blade‐like incisor on the left mandible implies the potential root cutting ability. Abstract : Larvae of Colobopterus quadratus were described using SEM. This study is the first attempt to discover the larval ultra‐morphology of Aphodiinae. The larvae are atypical for the clypeus bearing four protuberances.